Unveiling the Multielectron Acceptor Properties of π-Expanded Pyracylene: Reversible Boat to Chair Conversion - Zhu, Yikun; Borstelmann, Jan; Bertleff, Oliver; Bergner, John; Wei, Zheng; Neiß, Christian; Görling, Andreas; Kivala, Milan; Petrukhina, Marina A. (Journal of the American Chemical Society, 2024)
In this work, the chemical reduction of a hybrid pyracylene-hexa-peri-hexabenzocoronene (HPH) nanographene was investigated with different alkali metals (Na, K, Rb) to reveal its remarkable multielectron acceptor abilities. The UV-vis and 1H NMR spectroscopy monitoring of the stepwise reduction reactions supports the existence of all intermediate reduction states up to the hexaanion for HPH. Tuning the experimental conditions enabled the synthesis of the HPH anions with gradually increasing reduction states (up to −5) isolated with different alkali metal ions as crystalline materials. The single-crystal X-ray diffraction structure analysis demonstrates that the highly negatively charged HPH anions (−4 and −5) exhibit a drastic geometry change from boat-shaped (observed in the neutral parent, mono- and dianions) to a chair conformation, which was proved to be fully reversible by NMR spectroscopy. DFT calculations show that this geometry change is induced by an enhanced interaction between the coordinated metal ions and negatively charged HPH core in the chair conformation.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Conformation; Ethers; Ions; Redox reactions; Transfer reactions